Does Mucosal B1 Activation Result in the Accumulation of Peak IgM During Chronic Intrarectal SIVmac239 Exposure to Protect Chinese-Origin Rhesus Macaques From Disease Progression? - Cong, Zhe; Tong, Ling; Wang, Yuhong; Su, Aihua; Chen, Ting; Wei, Qiang; Xue, Jing; Qin, Chuan (Frontiers in Microbiology, 2020)
Human immunodeficiency virus (HIV) infection is characterized by a dynamic process and highly variable progression. Although extensive comparisons have been reported between the minority of nonprogressors (NPGs) and the majority of progressors (PGs), the underlying mechanism is still unclear. One reason for this is that the initial onset of infection is very difficult to track, particularly when men who have sex with men (MSM) are predominantly responsible for the transmission of human HIV. To find potential early protection strategies against later progression during chronic mucosal exposure, ten Chinese-origin rhesus macaques (ChRhs) that underwent repetitive simian immunodeficiency virus (SIV) intrarectal exposure were longitudinally tracked. The results of the periodic detection of peripheral blood mononuclear cells (PBMCs) and colorectal mucosal lamina propria mononuclear cells (LPMCs) with immunoglobulins in rectal fluid were compared between nonprogressive and progressive subgroups, which were classified based on their circulating viral loads. As a result, four NPGs and six PGs were observed after disease onset for two months. Upon comparing the mucosal and systemic immune responses, the PBMC response did not differ between the two subgroups. Regarding LPMCs, the increased activation of B1a/B1 cells among B cells and a peak in IgM in rectal fluid was observed approximately 10 days after the first exposure, followed by consistently low viremia in the four nonprogressive ChRhs. In the six progressive ChRhs, neither B cell activation nor a peak in IgM was observed, while a robust elevation in IgG was observed, followed by consistently high viremia post exposure. Based on the PBMC-LPMC disparity between the subgroups of monkeys, we hypothesize that early B1 activation in LPMCs that result in an IgM peak might attenuate the entry and acquisition of SIV in the mucosa, resulting in very low dissemination into blood. Our models have suggested that the use of early surveillance both systemically and in the mucosa to comprehensively determine virus-host interactions would be informative for mucosal vaccine development.